2020
DOI: 10.1186/s40337-020-00296-2
|View full text |Cite
|
Sign up to set email alerts
|

Re-inhabiting one’s body: A pilot study on the effects of dance movement therapy on body image and alexithymia in eating disorders

Abstract: Background: Body image disturbance and alexithymia are two core aspects of Eating Disorders (EDs). However, standard treatments for EDs do not include specific techniques to approach these issues on a bodily level. This pilot study evaluated the effects of a Dance Movement Therapy (DMT) intervention on body image and alexithymia in patients with EDs, and also explored their experience of the therapeutic process. Method: 14 patients with EDs were recruited from a private clinic. Seven were assigned via quasi-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
(81 reference statements)
1
19
0
1
Order By: Relevance
“…Thirteen studies were RCTs ( 49 53 , 56 – 63 ), 8 studies were NRCTs ( 8 , 64 70 ), and 6 studies were UTs ( 54 , 55 , 71 75 ). All studies included patients with a diagnosis of AN; 11 studies also included patients with other ED as well ( 58 60 , 62 , 63 , 66 , 69 , 70 , 72 74 ); while 16 of the 27 studies included only patients with AN ( 8 , 49 57 , 61 , 64 , 65 , 67 , 68 , 71 , 75 ). Ten studies were conducted with inpatients ( 49 , 50 , 60 , 62 , 64 , 66 , 68 , 69 , 74 , 75 ), 15 were conducted with outpatients ( 51 53 , 56 – 59 , 61 , 63 , 65 , 67 , 70 73 ) and 2 did not report the treatment setting ( 8 , 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were RCTs ( 49 53 , 56 – 63 ), 8 studies were NRCTs ( 8 , 64 70 ), and 6 studies were UTs ( 54 , 55 , 71 75 ). All studies included patients with a diagnosis of AN; 11 studies also included patients with other ED as well ( 58 60 , 62 , 63 , 66 , 69 , 70 , 72 74 ); while 16 of the 27 studies included only patients with AN ( 8 , 49 57 , 61 , 64 , 65 , 67 , 68 , 71 , 75 ). Ten studies were conducted with inpatients ( 49 , 50 , 60 , 62 , 64 , 66 , 68 , 69 , 74 , 75 ), 15 were conducted with outpatients ( 51 53 , 56 – 59 , 61 , 63 , 65 , 67 , 70 73 ) and 2 did not report the treatment setting ( 8 , 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…It demonstrated significant improvement in mood after each DMT session. There was a decreased sense of fear, improvement in the overall attitude and feeling of joy which helped them to fight the chronic disease with self-confidence [29].…”
Section: Discussionmentioning
confidence: 99%
“…The study was also declared to the Research Department of the University Hospital. The study was in accordance with the declaration of Helsinki [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since then, different meta-analyses have shown that muscle strength and function were improved without negative effects on anthropometric measurements (body weight and BMI) in the case of calorie intake adjustment [ 16 , 17 , 18 ]. The practice of physical activities could also improve body perception, eating disorder symptoms, mood, and quality of life [ 14 , 17 , 19 , 20 ]. However, controlling physical activities is essential because of the malnourished state of the subjects, who may also present hyperactivity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%